Assessing the determinants of customer-perceived value and customer satisfaction in e-hailing services: An Importance-Performance Matrix Analysis (IPMA) Approach - Emily H.T. Yapp; Jasmine A.L. Yeap (Cogent Business & Management, 2023)
The rapid growth and success of sharing economy, particularly e-hailing services, have attracted many organisations to participate in this business. As a result, e-hailing organisations need strategies that enable them to compete in the market. One of the strategies that could help e-hailing organisations to stay competitive is to understand users' perception of value. The aim of this study is to identify the values that users gain when they use e-hailing services. From there, this study also sought to determine the specific values, which contribute to satisfaction with e-hailing services. The Theory of Consumption Value was applied to examine as users' perceived value with the inclusion of sustainability value. Based on the Partial Least Squares analysis via the software SmartPLS 3.2.8, users' perceived value, which consists of economic value, convenience value, sustainability value, and hedonic value positively influences users' satisfaction, while symbolic value negatively influences users' satisfaction. The Importance-Performance Matrix Analysis (IPMA) results revealed that hedonic value is the most important value that contributes to users' satisfaction. Theoretical and managerial implications as well as research limitations are duly discussed.
Keywords: 650; e-hailing; IPMA; Millennials; Perceived value; satisfaction; sharing economy; Theory of Consumption Value